Corporate Governance and Financial Stability: A Case of Nepalese Commercial Banks - Khadka, Nisha; Lamichhane, Manisha; Tamang, Manju; Gautam, Nitisha; Khatiwoda, Pallawi; Pradhan, Sumit (Nepalese Journal of Finance, 2025)
The study examines the effect of corporate governance on financial stability of Nepalese commercial banks. Z score and return on equity are selected as the dependent variables. The selected independent variables are board size, board independence, audit committee size, institutional ownership, female directors and number of meetings. The study is based on secondary data of 10 commercial banks with 100 observations for the period from 2012/13 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the financial stability of Nepalese commercial banks. The study showed that board independence has a positive impact on Z score and return on equity. It implies that increase in number of independent directors in board leads to increase in Z score and return on equity. Similarly, audit committee size has a positive impact on Z score and return on equity. It implies that increase in audit committee size leads to increase in Z score and return on equity. However, board size has a negative impact on Z score and return on equity. It means that increase in board size leads to decrease in Z score and return on equity. Similarly, number of board meeting has a positive impact on Z score and return on equity. It shows that increase in board meeting leads to increase in Z score and return on equity. Similarly, female director has a positive impact on Z score and return on equity. It implies that increase in female board directors leads to increase in Z score and return on equity.